Prevalence and pathology of pancreatic disorders in cattle - Princy Thomas (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2000)
The present study was undertaken to assess the prevalence and various pathological disorders of the pancreas in cattle. One hundred pancreas collected from the slaughter house and autopsy specimens formed the basis of the study. Serum and urine samples were collected from the slaughtered animals for clinico- pathological evaluation. Fifty one per cent of the pancreas showed lesions of which, 17 per cent severe, 14 per cent showed moderate and 20 per cent showed mild lesions. It was observed that chronic